Effect of high hydrostatic pressure on enzyme activity in unpasteurized draft sake. Issue 2 (3rd April 2019) - Shigematsu, Toru; Okada, Nobuya; Nomura, Kazuki; Kataoka, Chihiro; (Ujiie) Hori, Saori; Takahashi, Iwao; Aoki, Toshio; Kuribayashi, Takashi; Kaneoke, Mitsuoki; Iguchi, Akinori
ABSTRACT: Unpasteurized draft sake has a potentially high market value, due to its fresh flavor and fruity taste, compared with conventional thermal-pasteurized sake . However, the shelf life of draft sake is limited. To increase the shelf life of draft sake, it is necessary to suppress flavor and taste deterioration resulting from inactivation of enzymes produced by koji -mold. Draft sake was treated with high hydrostatic pressure (HHP) of 200 to 500 MPa at −7 to 50°C to analyze the inactivation of α-amylases, glucose-forming enzymes, and acid carboxypeptidases. We found significant inactivation of enzymes produced by koji -mold in draft sake subjected to HHP treatment at both high and low temperature. However, HHP treatment at low temperature effectively inactivated enzymes while retaining the fresh flavor and fruity taste of draft sake .